Respuesta :

Answer:

(7, - 1 )

Step-by-step explanation:

Given the 2 equations

2x + 4y = 10 → (1)

- 2x + y = - 15 → (2)

Adding the 2 equations term by term eliminates the term in x, that is

5y = - 5 ( divide both sides by 5 )

y = - 1

Substitute y = - 1 into either of the 2 equations and solve for x

Substituting into (1)

2x + 4(- 1) = 10

2x - 4 = 10 ( add 4 to both sides )

2x = 14 ( divide both sides by 2 )

x = 7

Solution is (7, - 1 )

(7, - 1 )

Step-by-step explanation:

Given the 2 equations

2x + 4y = 10 → (1)

- 2x + y = - 15 → (2)

Adding the 2 equations term by term eliminates the term in x, that is

5y = - 5 ( divide both sides by 5 )

y = - 1

Substitute y = - 1 into either of the 2 equations and solve for x

Substituting into (1)

2x + 4(- 1) = 10

2x - 4 = 10 ( add 4 to both sides )

2x = 14 ( divide both sides by 2 )

x = 7

Solution is (7, - 1 )